Learn more about

Refine search

Results (displaying matches 1-50 of 24611) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
249.a.249.1 249.a \(y^2 + (x^3 + 1)y = x^2 + x\) $\mathrm{USp}(4)$ 0
277.a.277.1 277.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ 0
277.a.277.2 277.a \(y^2 + y = x^5 - 9x^4 + 14x^3 - 19x^2 + 11x - 6\) $\mathrm{USp}(4)$ 0
295.a.295.1 295.a \(y^2 + (x^3 + 1)y = -x^2\) $\mathrm{USp}(4)$ 0
295.a.295.2 295.a \(y^2 + (x^2 + x + 1)y = x^5 - 40x^3 + 22x^2 + 389x - 608\) $\mathrm{USp}(4)$ 0
349.a.349.1 349.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2\) $\mathrm{USp}(4)$ 0
363.a.43923.1 363.a \(y^2 + x^2y = 11x^5 - 13x^4 - 7x^3 + 10x^2 + x - 2\) $G_{3,3}$ 0
394.a.394.1 394.a \(y^2 + (x^3 + x)y = 2x^5 + x^4 - 12x^3 + 17x - 9\) $\mathrm{USp}(4)$ 0
461.a.461.1 461.a \(y^2 + x^3y = x^5 - 3x^3 + 3x - 2\) $\mathrm{USp}(4)$ 0
461.a.461.2 461.a \(y^2 + y = x^5 - x^4 - 39x^3 + 10x^2 + 272x - 306\) $\mathrm{USp}(4)$ 0
464.a.464.1 464.a \(y^2 + (x + 1)y = -x^6 - 2x^5 - 2x^4 - x^3\) $\mathrm{USp}(4)$ 0
472.a.60416.1 472.a \(y^2 + (x + 1)y = 8x^5 + 5x^4 + 4x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
597.a.597.1 597.a \(y^2 + y = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
604.a.9664.1 604.a \(y^2 + (x^2 + x + 1)y = 4x^5 + 9x^4 + 48x^3 - 4x^2 - 53x - 21\) $\mathrm{USp}(4)$ 0
604.a.9664.2 604.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
688.a.704512.1 688.a \(y^2 = 2x^5 + 4x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
708.a.2832.1 708.a \(y^2 + (x^2 + x + 1)y = x^5\) $\mathrm{USp}(4)$ 0
726.a.1452.1 726.a \(y^2 + (x^2 + 1)y = 2x^5 + 2x^4 + 6x^3 - 2x^2 - x\) $G_{3,3}$ 0
797.a.797.1 797.a \(y^2 + y = x^5 - x^4 + x^3\) $\mathrm{USp}(4)$ 0
810.a.196830.1 810.a \(y^2 + (x + 1)y = x^5 + 15x^4 + 20x^3 - 297x^2 + 94x - 8\) $N(G_{1,3})$ 0
830.a.6640.1 830.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 - 2x^2 + x + 1\) $\mathrm{USp}(4)$ 0
832.a.832.1 832.a \(y^2 + (x^3 + x)y = x^5 - x^3 + x^2 + 2x - 1\) $\mathrm{USp}(4)$ 0
834.a.1668.1 834.a \(y^2 + (x^3 + 1)y = -x^2 + x - 1\) $\mathrm{USp}(4)$ 0
847.b.9317.1 847.b \(y^2 + (x^2 + 1)y = x^5 + 2x^4 - 3x^3 + 2x^2 - x\) $G_{3,3}$ 0
847.c.9317.1 847.c \(y^2 + (x^3 + x^2)y = x^4 + x^3 - x - 2\) $\mathrm{USp}(4)$ 0
862.b.862.1 862.b \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - x - 1\) $\mathrm{USp}(4)$ 0
880.a.225280.1 880.a \(y^2 = x^5 + 13x^4 + 55x^3 + 76x^2 - 44\) $G_{3,3}$ 0
886.a.3544.1 886.a \(y^2 + (x^3 + x)y = -x^4 - x + 1\) $\mathrm{USp}(4)$ 0
971.a.971.1 971.a \(y^2 + y = x^5 - 2x^3 + x\) $\mathrm{USp}(4)$ 1
976.a.999424.1 976.a \(y^2 + (x + 1)y = x^6 - 2x^5 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 0
997.b.997.1 997.b \(y^2 + y = x^5 - 2x^4 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1012.a.4048.1 1012.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1038.a.1038.1 1038.a \(y^2 + (x^2 + x)y = x^5 - 12x^4 + 26x^3 + 46x^2 + 21x + 3\) $\mathrm{USp}(4)$ 0
1042.a.1042.1 1042.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 + 2x + 2\) $\mathrm{USp}(4)$ 0
1051.a.1051.1 1051.a \(y^2 + y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1055.a.1055.1 1055.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - x - 1\) $\mathrm{USp}(4)$ 0
1062.a.6372.1 1062.a \(y^2 + (x^3 + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1069.a.1069.1 1069.a \(y^2 + (x^2 + x + 1)y = x^5 + x^3\) $\mathrm{USp}(4)$ 0
1070.a.2140.1 1070.a \(y^2 + (x^3 + 1)y = x^3 - x\) $\mathrm{USp}(4)$ 1
1077.b.1077.1 1077.b \(y^2 + x^3y = x^5 + x^4 - x - 2\) $\mathrm{USp}(4)$ 0
1077.b.1077.2 1077.b \(y^2 + y = x^5 + 14x^4 + 38x^3 - 79x^2 + 15x - 1\) $\mathrm{USp}(4)$ 0
1091.a.1091.1 1091.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1094.a.2188.1 1094.a \(y^2 + (x^3 + 1)y = x^4 - x^2\) $\mathrm{USp}(4)$ 1
1104.a.17664.1 1104.a \(y^2 = x^5 - 2x^4 + 4x^3 - 4x^2 + 3x - 1\) $\mathrm{USp}(4)$ 0
1109.a.1109.1 1109.a \(y^2 + y = x^5 - 6x^4 - 36x^3 - 6x^2 + 63x - 36\) $\mathrm{USp}(4)$ 0
1109.b.1109.1 1109.b \(y^2 + y = x^5 - x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1109.c.1109.1 1109.c \(y^2 + (x^3 + x)y = x^5 - 2x^3 - 2x^2 - 1\) $\mathrm{USp}(4)$ 0
1136.a.290816.1 1136.a \(y^2 + (x^3 + x^2)y = -5x^4 - 9x^3 + 25x^2 + 40x - 24\) $\mathrm{USp}(4)$ 0
1137.a.1137.1 1137.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 + x^3\) $\mathrm{USp}(4)$ 0
1145.a.1145.1 1145.a \(y^2 + (x^3 + 1)y = -3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 1
Next

Download all search results for